STUDI PENGARUH UKURAN PIXEL IMAGING PLATE TERHADAP KUALITAS CITRA RADIOGRAF - Sudin, Ahmas; Muhlisin, Zaenul; Widiyandari, Hendri (BERKALA FISIKA, 2015)
This study aims is to determine the image on imaging plate which has a different pixel sizes. In this research, the X-ray apparatus and Computed Radiography (CR) which is used in the diagnostic field was used. The three imaging plate each having size of 0.097 mm, 0.115 mm and 0.168 mm with stepwedge objects on it was used. The exposure factor was adjusted at 64.5 kV and 16 mAs. The each of imaging plate were exposure three times. The results of each radiograph imaging plate were measured by using a densitometer. By measuring the Stepwedge radiograph, it was obtained the density and contrast value of each imaging plate. Contrast value for each imaging plate were compared to obtain the imaging plate that have a higher contrast value. This research resulted that each different pixel sizes on the imaging plate would generate a different image quality. Keywords: pixel, imaging plate, image quality, contras, density